High-performance liquid chromatography method for the determination of levofloxacin in liquid pharmaceutical preparations: Implications for environmental health and earth sciences - Smanova Zulayho; Arazberdieva Shemshat; Abdullaeva Muborek; Akhmadjanov Ulugbek (E3S Web of Conferences)
Analytical testing is integral to evaluating pharmaceutical quality and efficacy, with important ramifications for both public health and environmental protection. This study details the development and validation of an HPLC method for quantifying levofloxacin in liquid pharmaceutical formulations, employing a 5 μm (150 × 3.9 mm) C18 reversed-phase column and a UV-visible detector. Gradient chromatography was performed over 25 minutes at a flow rate of 1.0 mL/min, with detection at 275 nm. Method validation used OpenLab ChemStation ver. A.01.05 and adhered to international guidelines, confirming the approach’s accuracy, linearity, specificity, and robustness. The results have implications for monitoring pharmaceutical residues in the environment, which is critical to safeguarding water resources and maintaining ecological balance in Earth sciences.